Idiopathic mesenteric phlebosclerosis associated with long-term use of Chinese herbal medicine - Yeh, Hsing-Jung; Lin, Pao-Ying; Kao, Wei-Yu; Kun, Ching-Huei; Chang, Chun-Chao (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Yeh HJ, Lin PY, Kao WY, Kun CH, Chang CC. Idiopathic mesenteric phlebosclerosis associated with long-term use of Chinese herbal medicine. Turk J Gastroenterol 2018; 29: 136-8.